Management of maritime boundaries: the case of Costa Rica and Nicaragua in the Pacific. [In Spanish with English abstract] - Murillo-Zamora, Carlos (2021)
Introduction: Public management has acquired new characteristics because of change in the way governance is approached. As the subject areas, levels and scales of this management have expanded, public administration has become more complex, requiring new approaches. Although the Law of the Sea and the thesis that the land dominates the sea are not new, the truth is that it was with the United Nations Convention of the Law of the Sea, of 1982, that the areas under the jurisdiction of the coastal States were formalized and institutionalized. This has generated new challenges for the governments, since not only does territorial sovereignty extend over a large portion of the sea, but new responsibilities are assumed on behalf of the international community. Objective: The matter links public management with the regulations of the Law of the Sea regarding the delimitation and administration of boundaries. Therefore, this review proposes an approach to a matter that has not been explored enough. Methods: A reviewof the literature on public border management was made, considering the case of maritime boundaries, identifying international jurisprudence -especially of the International Court of Justice- and actions implemented by Costa Rica. Results: in the land portion, border management shows important development; this is not the case in the maritime spaces. The jurisdiction is different in each of these spaces, so public management must take these particularities into account. Things get complicated when it comes to the border area, because in it the marine and the maritime converge, but also different interests, due to the nature of the marine space. Therefore, it is necessary to recognize that the management of maritime boundaries is not as simple as moving what is done on land to the sea. When the limit was defined by a bilateral treaty, some provisions facilitate cross-border coordination and cooperation. For this reason, the case of Costa Rica and Nicaragua in the Pacific Ocean was used as a reference, since in this case the dividing line was established by the International Court of Justice, which causes a layout that is not necessarily satisfactory for the actors involved. Conclusions: the differences in border management between land and sea, in addition to how the boundary between the two countries is defined, has made it difficult for Costa Rica to implement public management, which is the best-known experience in the region on marine-maritime policies and management.